Implicit affectivity and rapid processing of affective body language: An fMRI study. Issue 5 (1st June 2015) - Suslow, Thomas; Ihme, Klas; Quirin, Markus; Lichev, Vladimir; Rosenberg, Nicole; Bauer, Jochen; Bomberg, Luise; Kersting, Anette; Hoffmann, Karl‐Titus; Lobsien, Donald
Abstract : Previous research has revealed affect‐congruity effects for the recognition of affects from faces. Little is known about the impact of affect on the perception of body language. The aim of the present study was to investigate the relationship of implicit (versus explicit) affectivity with the recognition of briefly presented affective body expressions. Implicit affectivity, which can be measured using indirect assessment methods, has been found to be more predictive of spontaneous physiological reactions than explicit (self‐reported) affect. Thirty‐four healthy women had to label the expression of body postures (angry, fearful, happy, or neutral) presented for 66 ms and masked by a neutral body posture in a forced‐choice format while undergoing functional magnetic resonance imaging (fMRI). Participants' implicit affectivity was assessed using the Implicit Positive and Negative Affect Test. Measures of explicit state and trait affectivity were also administered. Analysis of the fMRI data was focused on a subcortical network involved in the rapid perception of affective body expressions. Only implicit negative affect (but not explicit affect) was correlated with correct labeling performance for angry body posture. As expected, implicit negative affect was positively associated with activation of the subcortical network in response to fearful and angry expression (compared to neutral expression). Responses of the caudate nucleus to affective body expression were especially associated with its recognition. It appears that processes of rapid recognition of affects from body postures could be facilitated by an individual's implicit negative affect.